What’s in a Name?: Tiglath-Pileser (The Biblical archaeology review, 2025)
Tukultī-apil-Ešarra Tukult.ī = "my trust" | apil = "heir of" | Ešarra = "Esharra temple" Tukultī-apil-Ešarra is an Akkadian royal name attested in written sources from ancient Assyria and neighboring regions, including Israel and Judah. Its modern spelling, Tiglath-Pileser, is adopted from the Hebrew Bible (2 Kings 15:29), where it appears also as Tilgath-Pilneser (2 […]